Addition of PD-1/PD-L1 inhibitors to chemotherapy for triple-negative breast cancer: a meta-analysis - Yang, Juan; Liu, Chen; Guo, Yaru; Guo, Wenwen; Wu, Xiaojin (Frontiers in Oncology, 2024)
In recent years, the addition of immune checkpoint inhibitors (ICI) to chemotherapy (CT) has become a research hotspot in the therapy of metastatic triple-negative breast cancer. Nevertheless, controversial results have been revealed among the published randomized controlled trials. Hence, a meta-analysis was performed to assess the therapeutic effect of this treatment regimen. Methods: Five English databases (PubMed, WOS, CENTRAL, Scopus, and Embase), and four Chinese databases (CBM, CNKI, VIP, and Wanfang), as well as oncological meetings, were systematically searched to identify eligible studies that assessed the addition of ICI to CT versus CT alone in metastatic triple-negative breast cancer. The pooled hazard ratios (HR) of progression-free survival (PFS) and overall survival (OS) were estimated using fixed- or random-effect model. Subgroup analyses were also performed in the intention-to-treat (ITT) and PD-L1-positive individuals. Results: All told there are five eligible randomized controlled trials involving 3,000 patients were enrolled in this meta-analysis. Compared with CT alone, the ICI plus CT regimen significantly increased PFS in the ITT (HR = 0.80, 95% CI: 0.73–0.88) and PD-L1-positive (HR = 0.70, 95% CI: 0.62–0.79) populations, as well as OS in the ITT (HR = 0.89, 95% CI: 0.81–0.97) and PD-L1-positive populations (HR = 0.80, 95% CI: 0.71–0.91). Moreover, the PFS of sufferers treated with the combination strategy of ICI with CT increased alongside PD-L1 enrichment. A clinical benefit in terms of objective response rate was also distinctly observed in both populations treated with ICI plus CT. In the subgroup analysis, patients in the no prior CT subgroup experienced a striking increase in PFS in both populations; however, a difference was not observed in other subgroups. Conclusions: The combination strategy striking improves PFS and OS in both ITT and PD-L1-positive populations, and PFS is prolonged with PD-L1 enrichment. Patients who do not receive CT prior to this treatment are associated with longer PFS in both populations.